Impact of a health alert and its implementation on flutamide prescriptions for women: an interrupted time series analysis - Raquel Vázquez-Mourelle; Eduardo Carracedo-Martínez; Adolfo Figueiras (BMC, 2020)
Abstract Background Off-label drug use among ambulatory patients is often based on little or no scientific support. This paper reports the impact of a health warning about the risks of off-label flutamide use by women and the actions subsequently implemented by the public health service targeting such use. Method The study was undertaken in a region in north-west Spain. We designed a segmented regression model of an interrupted time series, in which the dependent variable was the monthly value of defined daily doses of flutamide per 1000 inhabitants/day (DDD/TID), both total and stratified by sex. The following two data sources were used: flutamide prescriptions billed to the Spanish National Health Service; and flutamide deliveries made by wholesale drug distributors to pharmacies. The intervention assessed consisted of the issue of an official health warning and the actions subsequently taken to implement it. Results There was an immediate reduction of 49.33% in DDD/TID billed to the Spanish National Health Service in respect of women; the mean value of the population percentage of DDD/TID of flutamide billed in respect of women fell from 34.4% pre-intervention to 23.72% post-intervention. There was an immediate reduction of 19.92% (95%CI: 6.68-33.15%) in total DDD/TID invoiced. There were no significant changes in DDD/TID billed in respect of men or in flutamide use in the private medical sector. Conclusions Off-label drug misuse is a reality among ambulatory patients, even after actions are implemented following a toxicity warning issued by the competent Health Authority.